Indonesia Comic Video Learning Media on Animal Ecosystem Material to Improve Science Learning Outcomes in Grade V Elementary School Students: Indonesia - I Kadek Aris Prayoga; Basilius Redan Werang; I Nyoman Jampel (Jurnal Media dan Teknologi Pendidikan, 2025)
This study was motivated by the low learning outcomes of students in the subject of Natural and Social Sciences (IPAS), particularly on the topic of animal ecosystems, due to the limited availability of interactive and engaging learning media. The aim of this research is to develop and evaluate the feasibility and effectiveness of comic video media as a visual learning alternative to support IPAS instruction. The study employed the ADDIE development model, which includes five stages: analysis, design, development, implementation, and evaluation. Data were collected through expert validation (media and content), practicality testing by teachers and students, and effectiveness testing through learning outcome assessments. Validation results indicated that the comic video media is highly valid, with average scores of 4.5 from media experts and 4.6 from content experts. The practicality was rated very good by teachers (4.72), small student groups (4.57), and individual students (4.75). Effectiveness testing showed significant results with a p-value of 6.476 × 10⁻¹² (p < 0.05). Therefore, the comic video is proven to be valid, practical, and effective in improving student learning outcomes in IPAS.